(untitled) (Construction Economics and Building, 2020)
Despite the fast growth of project-based companies and industries, studies of the satisfaction-performance (S-P) nexus of project participants are lacking. This study aims to explore the role of contractor satisfaction in affecting contractor project management performance along with considering external effects from other key participants. Two broad dimensions of satisfaction toward noneconomic factors and economic factors were used to develop hypothesized models. Structural equation modelling techniques were applied with data collected from 117 projects, showing that it is insufficient to simply conclude that contractor satisfaction influences project managerial performance and vice versa, and that satisfaction disaggregation is necessary. Additionally, it was found that noneconomic satisfaction contributes to performance, which in turn contributes to economic satisfaction. The theoretical and practical implications are further discussed.